Unorganised workers: deprivation, social security needs, policy implications - Rao, V.M. Rajasekhar, D.; Suchitra, J.Y. (2006)
Provision of social security to the unorganised workers is currently receiving the urgent attention of the central government and some of the state governments. This paper, based on a large sample of unorganised workers - construction worker, domestic workers and agricultural labourers - from Karnataka, presents indices of their economic conditions and deprivation to show hos inadequate it is to use the below poverty line criterion for providing benefits to unorganised sector workers. The priority social security needs are analysed to show the diversity within and across sectors, and to review the policy measures - existing and those on the anvil. - Reproduced.
Keywords: Workers; Social security